PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK PAKAIAN DI MATAHARI PALEMBANG SQUARE EXTENSION - M.dwi yanputra; dian eka; aslamia rosa (JEMBATAN, 2017)
The main objective of this study was to determine the effect of the promotionmix terhdap purchasing decisions apparel products in Matahari Palembang SquareExtension. The research sample of 100 respondents from consumer Sun PalembangSquare. The sampling method used was non-probability sampling for consumers fromthe Sun varies. The coefficient of determination shows that 58.2% of the productpurchase decision influenced by variables clothing promotion (advertising, personalselling, publicity, sales promotion and direct marketing). Mechanical data used ismultiple regression analysis. The results showed that the simultaneous promotion mixinfluence on purchase decisions apparel products. Partial publicity only variable thatdoes not have significant influence on purchasing decisions apparel products inMatahari Palembang Square Extension.Keyword : Mix Promotions, Products Clothing, Purchase Decision.